Adjacency Pair Of The Characters Utterances In Breaking Bad TV Series - Nazira, Siti; Artawa, Ketut; Malini, Ni Luh Nyoman Seri (International Journal of Linguistics and Discourse Analytics, 2025)
Language plays a vital role in daily interaction, enabling people to convey meaning, build relationships, and coordinate social actions. In spoken discourse, adjacency pairs function as key structural units that organize conversation and guide turn-taking. Although conversational analysis has been widely explored in linguistic theory, its application to authentic or scripted dialogue—particularly in popular media—remains limited. This study addresses that gap by analyzing how adjacency pairs operate in exchanges between Walter White and Jesse Pinkman in the TV series Breaking Bad. The research identifies the types of adjacency pairs used and examines how the characters respond to each other’s utterances. Using a qualitative descriptive method, the study analyzes transcriptions from the third season and categorizes data based on established adjacency pair types. The findings show that all types appear, with question–answer and request–accept/refuse pairs occurring most frequently. Overall, the study demonstrates how fictional dialogue mirrors real conversational patterns and reveals character dynamics.